2017
DOI: 10.1038/ijir.2017.9
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between peak systolic velocity and diameter of cavernosal arteries in flaccid versus dynamic state for the evaluation of erectile dysfunction

Abstract: Previous studies have suggested that parameters measured in the flaccid state (FS) by penile duplex Doppler ultrasound (PDDU) may predict the outcome after intracavernosal injection (ICI). The aim of this study was to evaluate the association between peak systolic velocity (PSV) and cavernosal artery diameter (CAD) in the FS with PSV and clinical assessment of erection hardness (CAEH) after ICI. Fifty patients who underwent PDDU for erectile dysfunction were prospectively enrolled. PSV and CAD were measured in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In order to avoid these disadvantages, measuring PSV in the flaccid state were applied. The correlation of the PSV value between flaccid state and erectile state were found by their study (Souper et al., 2017). A study showed that flaccid PSV <13 cm/s predicts reduced dynamic PSV with an accuracy >80% (Corona et al., 2008).…”
Section: Discussionmentioning
confidence: 75%
“…In order to avoid these disadvantages, measuring PSV in the flaccid state were applied. The correlation of the PSV value between flaccid state and erectile state were found by their study (Souper et al., 2017). A study showed that flaccid PSV <13 cm/s predicts reduced dynamic PSV with an accuracy >80% (Corona et al., 2008).…”
Section: Discussionmentioning
confidence: 75%
“…Combined audiovisual sexual stimulation and intra-cavernous injections would not only increase the objective response of penile erection but also improve subjective sexual arousal and satisfaction by providing a comfortable environment (40). Although there is a consensus in guidelines to use CDDU to detect dynamic parameters after intra-cavernous injections (41), recent studies have claimed that PSV in a flaccid state also has a good predictive value for arterial dysfunction (51,52). A study of 1,346 male patients found that the diagnostic accuracy of PSV with 13 cm/s as the threshold in flaccid state was more than 80% (53).…”
Section: Cddumentioning
confidence: 99%